Integrative multi-omics analysis reveals genetic and epigenetic regulatory networks of body weight in the mud crab (Scylla paramamosain) - Qionghui Qin; Weiren Zhang; Meiling Liang; Yijia Shih; Yaodong Zhang; Siyi Zhou; Kewei Huang; Xiaopeng Wang; Haihui Ye (Aquaculture, 2027)

Gram-scale production of forskolin in yeast through biosynthetic network elucidation and pathway optimization - Meiling Jiang; Hao Tang; Ying Ma; Zhenjiang Tian; Wenbo Xu; Xinqi Song; Lan Kang; Luqi Huang; Yating Hu (Bioresource Technology, 2026)

Liensinine can improve vascular remodeling in hypertension through the ferroptosis-related TLR4 inflammatory pathway - Daxin Chen; Peizhi Jia; Meiling Wang; Baojie Du; Haitao Du; Xi Huang; Jianwei Zeng; Qiaoyan Cai; Ling Zhang; Ying Zhu; Shan Lin; Dawei Lian; et al. (Journal of Molecular Medicine, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

An NSGA-III–based predict–optimize–evaluate framework for low carbon land use optimization: A case study of the Yangtze River Delta - Menglin Yu; Jie Tao; Peng Zhang; Meiling Zhou; Beiying Huang; Jie Guo; Jialin Yi (Journal of Environmental Management, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Facet and crystallinity-dependent transformation of lepidocrocite impacts cadmium redistribution - Meiling Yin; Jin Wang; Songxiong Zhong; Xiaofei Li; Fei Huang; Chen Yang; Fangbai Li; Zhi Dang; Chuling Guo (Environmental Pollution, 2026)

Zwitterionic polyurethane-based solid polymer electrolytes for high-performance solid-state Lithium metal batteries - Jiaxing Liu; Bei Deng; Meiling Liu; Yaxue Zhang; Zhihao Yang; Tieqi Huang; Hongtao Liu (Chemical Engineering Journal, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

Deciphering the mechanisms of phosphorus concentration in regulating nitrogen removal and autoaggregation of Pseudomonas stutzeri - Hanbo Zhao; Jie Huang; Meiling Tong; Yanghua Ou; Zhixuan Yu; Xiaowei Xu; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2026)

Bridging data gaps in landslide early warning: Physics-derived rainfall thresholds under rainfall uncertainty - Hao Zou; Weiye Huang; Ting Liu; Henghao Cai; Shuai Mao; Bing Chen; Meiling Wu; Qingyu Zhang; Xiao Liu; Shu Zhang (Engineering Geology, 2026)

Coupled crack-rainfall mechanism of a retrogressive landslide: field investigation and monitoring in Southwest China - Qiuxiang Huang; Shupeng Li; Meiling Xiong; Chu Zhang; Yan Zhou (Bulletin of Engineering Geology and the Environment, 2026)

Pore Structure Characteristics and Controlling Factors of Different Lithofacies in Lacustrine Shale: A Case Study of Fengcheng Formation in Mahu Sag, Junggar Basin - Jiahao Lyu; Fujie Jiang; Jing Xue; Tao Hu; Yuping Wu; Chenxi Zhang; Meiling Hu; Renda Huang (Journal of Earth Science, 2026)

Investigation of Oil Content in Lacustrine Shale-Oil Systems: Insights from Two Different Pyrolysis - Yuping Wu; Chenglin Liu; Fujie Jiang; Tao Hu; Chenxi Zhang; Jiahao Lyu; Renda Huang; Meiling Hu; Guanyun Wu; Rizwan Sarwar Awan (Journal of Earth Science, 2026)

Alleviating Clostridium perfringens-Induced Gut Lesionsin Broiler Chickens by Orally Administered Bovine Intestinal Alkaline Phosphatase - Wangli Ji; Daoxin Yang; Wenjing Zhang; Yuan Wang; Zhenzhen Hao; Kairui Guo; Xianhua Sun; Shuai Wang; Shuyan Yang; Jianshuang Ma; Huiying Luo; Bin Yao; et al. (Probiotics and Antimicrobial Proteins, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Predicting ecological risks of heavy metals in watersheds based on interpretable machine learning models: under the framework of data scarcity - Hong Chen; Meiling Kong; Zhenghua Wu; Liu Gong; Lanlan Huang; Yihan Li; Fazhi Xie (Environmental Monitoring and Assessment, 2026)

Comparative assessment of female reproductive toxicity from PFOA and its alternative GenX in mice and human granulosa cells - Yangyang Yuan; Binhui Wang; Yuyu Fan; Meiling Le; Lihai Wu; Shiyi Deng; Jian Huang; Dalei Zhang (Toxicology and Applied Pharmacology, 2026)

Characterization of a myoinhibitory peptide and its role in neuroimmune regulation in Litopenaeus vannamei during Vibrio harveyi infection - Yongxiong Huang; Meiling Huang; XuYan Tan; Zhiqiang Zhang; Jia Cai; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Numerical simulation of wind field characteristics and enhanced heat exchange performance for the novel bucket-shaped anti-frosting evaporator - Guodong Qiu; Meiling Huang; Dan Liu; Yanfeng Chen; Weihua Cai (International Journal of Refrigeration, 2025)

FeOOH@HAnB catalyst with exposed (211) facet: High stability and new degradation routes for tetracycline - Yingru Huang; Meiling Zhou; Yaping Zhang; Yufeng He; Yuanyuan Xie; Rongmin Wang (Environmental Research, 2025)

Long-term nitrogen enrichment affects soil organic carbon fractions through microbial pathways in fluvo-aquic soil - Binggeng YANG; Jiwen CUI; Meiling ZHANG; Kangrui FANG; Chao AI; Tengfei GUO; Shaomin HUANG; Dali SONG; Wei ZHOU (Pedosphere, 2025)

Possible influences of tropical vegetation shift on the glacial-interglacial temperature changes - Liping Tian; Cong Chen; Mengyuan Wang; Chuanxiu Luo; Xiao Zhang; Yanming Ruan; Jiantao Cao; Meiling Man; Zhuo Zheng; Xiaoqiang Yang; Kangyou Huang; Li Li; et al. (Global and Planetary Change, 2025)

Study on the evolution and prediction of carbon emission from land use change in Tulufan-Hami basin under the influence of urbanization and climate change - Meiling Huang; Yusuyunjiang Mamitimin; Abudukeyimu Abulizi; Rebiya Yimaer; Bahejiayinaer Tiemuerbieke; Han Chen; Tongtong Tao; Yunfei Ma (Environment, Development and Sustainability, 2025)

Environmental Impacts and Behaviors of Chromium in Pakchoi-Soil Systems Under Ambient and Elevated CO2 Levels - Yuning Wang; Yatu Huang; Ye Ding; Wentao Yang; Yabo Wang; Qiao Xu; Yao Yao; Xiaozhi Wang; Meiling Xu (Water, Air, & Soil Pollution, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Hypoxia-activated and status-reversing hydrogel platform initiates potent systemic immunity against triple-negative breast cancer - Zhike Li; Xianzhou Huang; Jin Yang; Meiling Shen; Yanjie You; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Revealing the key organelle in the pathophysiology and clinical applications of animal toxins: Mitochondria - Linfeng Wang; Jiahao Liu; Sheng Zhou; Jiaqi Sun; Meiling Liu; Jianqi Zhao; Lixia Cheng; Zejing Wen; Xiaowen Bi; Chunhong Huang (Toxicon, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Characteristics, sources, and health risks of fine particulate matter in Wuhan subway, China - Ji-Liang Lü; Qing Han; Zhen Wang; Min Tao; Xun Hu; Meiling Cao; Qingzhu Huang; Mengdie Shi; Zhenyu He; Xiaohu Zhao (Science of The Total Environment, 2025)

Dietary arabinogalactan modulates immunity and improves gut barrier in broilers via regulating metabolome and gut microbiome - Yafei Liu; Qingxiu Liu; Miaolin Ma; Jiatu Zhang; Meiling Liu; Rainer Mosenthin; Lihong Zhao; Shimeng Huang; Qiugang Ma (Carbohydrate Polymers, 2025)

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

Dual-mode detection of human immunoglobulin via copper oxide nanozyme catalysis fluorescent species generation and photoelectrochemical alteration in ZnIn2S4/SnO2-based system - Jiawei Zhou; Lili Zhao; Yuee Zhong; Peipei Li; Xiaohua Zhu; Shu Huang; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2025)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

MicroRNA expression profiles in plasma exosomes of late pregnant giant pandas - Meiling Cheng; Yingmin Zhou; Qian Wang; Bo Luo; Yanwu Lai; Jianbin Cheng; Xiuyue Zhang; Yan Huang; Desheng Li (Molecular Biology Reports, 2024)

Analytical and numerical study on the dynamic responses of the buried offshore oval lined-pipeline system under strike-slip fault - Zhaochao Li; Shiyi Zhang; Meiling Shen; Hao Huang (Ocean Engineering, 2024)

Thermal upheaval buckling framework of a graphene-reinforced subsea pipeline laid on an arched concave seabed - Zhaochao Li; Di Hu; Meiling Shen; Hao Huang; Zhihua Ou (Engineering Structures, 2024)

New perspective for pathomechanism and clinical applications of animal toxins: Programmed cell death - Jiaqi Sun; Jiahao Liu; Meiling Liu; Xiaowen Bi; Chunhong Huang (Toxicon, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

The immune function of heme oxygenase-1 (HO-1) from Nile tilapia (Oreochromis niloticus) in response to bacterial infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Adsorption Performance of Chitosan and Glutaraldehyde Modified Biochars for Trivalent Antimony in Acidic Wastewater - Huifang Lei; Nora F. Y. Tam; Xinhua Geng; Meiling Zhong; Xiaolan Lao; Xiaotong Su; Xuexia Huang; Lezhang Wei; Yu Liu; Qihang Wu; Ying-heng Fei; Dinggui Luo; et al. (Water, Air, & Soil Pollution, 2024)

Subalpine peatland development since the Last Glacial Maximum in subtropical China: Predominantly controlled by monsoonal climate and local topography - Cong Chen; Kangyou Huang; Dehao Xie; Meiling Man; Yongjie Tang; Yuanfu Yue; Xiao Zhang; Zhuo Zheng; Rachid Cheddadi (CATENA, 2024)

Microbial role in enhancing transfer of straw-derived nitrogen to wheat under nitrogen fertilization - Shuyu Huang; Xue Gao; Li Zeng; Meiling Zhang; Liyu Zhang; Shiyu Wang; Yuanzheng Zhao; Wei Zhou; Chao Ai (Soil and Tillage Research, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

All-in-one treatment: Capture and immobilization of 137Cs by ultra-stable inorganic solid acid materials HMMoO6·nH2O (M = Ta, Nb) - Zhihua Chen; Shaoqing Jia; Haiyan Sun; Junhao Tang; Yanling Guo; Yuexin Yao; Tianyu Pan; Meiling Feng; Xiaoying Huang (Water Research, 2024)

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Utilizing different types of biomass materials to modify steel slag for the preparation of composite materials used in the adsorption and solidification of Pb in solutions and soil - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Fanmin Zhu; Zhanbin Huang (Science of The Total Environment, 2024)

A novel method to advance the brGDGTs-based paleoclimate reconstruction applicable to different terrestrial environments - Liping Tian; Mengyuan Wang; Cong Chen; Xiao Zhang; Zhuo Zheng; Meiling Man; Kangyou Huang; Li Li; Guodong Jia (Quaternary Science Reviews, 2024)

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Molecular characteristics and functional analysis of non-specific cytotoxic cell receptor (NCCRP1) in golden pompano (Trachinotus ovatus) - Meiling Huang; Zhiqiang Zhang; Xing Li; Jiamin Feng; Yongxiong Huang; Amoah Kwaku; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

The stable carbon and hydrogen isotopic composition of microbial fatty acids traces microbial metabolism in soils and peats - Yiming Zhang; B. David A. Naafs; Xianyu Huang; Meiling Zhao; Linghan Zeng; Jerome Blewett; Richard D. Pancost; Shucheng Xie (Geochimica et Cosmochimica Acta, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Intrinsic photothermal phase change materials with enhanced toughness and flexibility for thermal management in extreme environments - Meiling Cui; Chong Tian; Yunyun Yang; Lei Huang; Qiang Liu; Na Yang; Fuqi Zhao; Xufu Cai; Weibo Kong (Chemical Engineering Journal, 2023)

Experimental and mechanistic study on the removal of lead from solution by sulfuric acid modified steel slag adsorbent - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Study on the effect of KMnO4−modified humic acid residues on the removal of Hg(Ⅱ)/Pb(Ⅱ) from solution - Yingnan Wang; Lingjian Kong; Meiling Wu; Haoran Ma; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Apolipoprotein Eb (On-ApoEb) protects Oreochromis niloticus against Streptococcus agalactiae infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Interleukin-8 involved in Nile Tilapia (Oreochromis niloticus) against bacterial infection - Xing Li; Baijian Jiang; Zhiqiang Zhang; Meiling Huang; Jiamin Feng; Yongxiong Huang; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Dorsal and ventral fronto-amygdala networks underlie risky decision-making in age-related cognitive decline - Ping Ren; Manxiu Ma; Yuchuan Zhuang; Jiayin Huang; Meiling Tan; Donghui Wu; Guozhi Luo (GeroScience, 2023)
Older adults often have difficulty in making decisions under uncertainty, increasing the risk of financial exploitation. However, it is still under investigation about the extent to which cognitive decline influences risky decision-making and the underlying neural correlates. We hypothesized that the individual differences of risk-taking behavior depend on cognitive integrity, in which the dorsal and ventral fronto-amygdala connectivity would play dissociable roles. In the current study, thirty-six young and 51 older adults were tested with the Iowa gambling task combing resting-state and task-related functional magnetic resonance imaging. The results showed significant changes in behaviors and the fronto-amygdala network in older adults relative to young adults. More importantly, age-effect on risk-taking behaviors was remarkably different in cognitively normal and impaired older adults. In resting-state analysis, task performance was positively correlated with the ventral fronto-amygdala connectivity and negatively correlated with the dorsal fronto-amygdala connectivity in cognitively impaired older adults, compared with cognitively normal individuals. Furthermore, task-related analysis confirmed the relationships between dorsal/ventral fronto-amygdala network and risk-taking behaviors depending on cognitive integrity. These findings indicate that the fronto-amygdala network is crucial for understanding altered risky decision-making in aging, suggesting dissociable contributions of the dorsal and ventral pathways in the context of cognitive decline.

Dose-response relationship of elements with blood lipids and the potential interaction: A cross-sectional study from four areas with different pollution levels in China - Shaoyi Chen; Muyang Zhang; Lidan Duan; Meiling Chen; Yuwei Du; Yuhan Cao; Zhijun Huang; Jia Zhao; Yanying Duan (Journal of Trace Elements in Medicine and Biology, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Baicalein ameliorates polymyxin B-induced acute renal injury by inhibiting ferroptosis via regulation of SIRT1/p53 acetylation - Meiling Yu; Hongyu Li; Boying Wang; Zhenxiang Wu; Sheng Wu; Guojun Jiang; Huaxue Wang; Yingying Huang (Chemico-Biological Interactions, 2023)

Design and synthesis of peptide-drug conjugates to double target EGFR - Xiaozhuo Tan; Meiling Le; Haiwen Wang; Bitao Huo; Tiantian Yu; Peng Huang; Tiangang Luan; Shijun Wen (Phytochemistry Letters, 2023)

Oil occurrence state and quantity in alkaline lacustrine shale using a high-frequency NMR technique - Chenxi Zhang; Fujie Jiang; Tao Hu; Di Chen; Liliang Huang; Zhenxue Jiang; Xiaohao Wang; Zheyu Liu; Yuping Wu; Jiahao Lv; Renda Huang; Meiling Hu; et al. (Marine and Petroleum Geology, 2023)

A novel perlucin-like protein (PLP) protects Litopenaeus vannamei against Vibrio harveyi infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Junliang Luo; Liwen Que; Shiping Yang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Involvement of CD27 in innate and adaptive immunities of Nile tilapia (Oreochromis niloticus) - Baijian Jiang; Qi Li; Zhiqiang Zhang; Yongxiong Huang; Yiqin Wu; Xing Li; Meiling Huang; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Efficacy and safety of IL-23 inhibitors in the treatment of psoriatic arthritis: a meta-analysis based on randomized controlled trials - Xiaojing Huang; Haojie Shentu; Yujing He; Haijia Lai; Chen Xu; Meiling Chen; Haowei Zhu (Immunologic Research, 2023)
In recent years, the use of interleukin (IL) 23 inhibitors in the treatment of psoriatic arthritis (PsA) has been the subject of much research. By specifically binding to the p19 subunit of IL-23, IL-23 inhibitors block downstream signaling pathways and inhibit inflammatory responses. The objective of this study was to assess the clinical efficacy and safety of IL-23 inhibitors in the treatment of PsA. PubMed, Web of Science, Cochrane Library, and EMBASE databases were searched from the time of conception to June 2022 for randomized controlled trials (RCTs) investigating the use of IL-23 in PsA therapy. The main outcome of interest was the American College of Rheumatology 20 (ACR20) response rate at week 24. We included six RCTs (3 studies on guselkumab, 2 on risankizumab, and 1 on tildrakizumab) with a total of 2971 PsA patients in our meta-analysis. We found that the IL-23 inhibitor group showed a significantly higher ACR20 response rate compared to the placebo group (relative risk = 1.74, 95% confidence interval: 1.57–1.92; P < 0.001; I 2 = 40%). There was no statistical difference in the risk of adverse events ( P = 0.07) and serious adverse events ( P = 0.20) between the IL-23 inhibitor and placebo groups. Notably, the rate of elevated transaminases in the IL-23 inhibitor group was higher than the placebo group (relative risk = 1.69; 95%CI 1.29–2.23; P < 0.001; I 2 = 24%). In the treatment of PsA, IL-23 inhibitors significantly outperform placebo intervention while maintaining a favorable safety profile.

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

Ferroptosis is involved in polymyxin B-induced acute kidney injury via activation of p53 - Hongyu Li; Boying Wang; Sheng Wu; Shuying Dong; Guojun Jiang; Yingying Huang; Xuhui Tong; Meiling Yu (Chemico-Biological Interactions, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Molecular characterization and functional analysis of CD209E from Nile Tilapia (Oreochromis Niloticus) involved in immune response to bacterial infection - Yiqin Wu; Meiling Huang; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Astrochronology and carbon-isotope stratigraphy of the Fengcheng Formation, Junggar Basin: Terrestrial evidence for the Carboniferous-Permian Boundary - Renda Huang; Fujie Jiang; Di Chen; Ruoyuan Qiu; Tao Hu; Linhao Fang; Meiling Hu; Guanyun Wu; Chenxi Zhang; Jiahao Lv; Yuping Wu; Liliang Huang (Gondwana Research, 2023)

A Quad-Functional On-demand released nanomissile achieves cascade amplification therapy of Triple-Negative breast cancer through reversing multiple resistance - Yan Wang; Xianzhou Huang; Shunyao Zhu; Lu Li; Jin Yang; Jie Li; Li Wang; Shuang Ma; Meiling Shen; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

How do fish functional traits respond to dams at the global scale? - Meiling Chen; Yangyang Liang; Xinyu Cheng; Jun Wang; Liuyong Ding; Minrui Huang; Guojing Wang; Juan Tao; Chengzhi Ding (Hydrobiologia, 2023)

Impaired barrier integrity of endothelial cells induced by PEGylated black phosphorus nanosheets - Jiayan Chen; Weiwei Huan; Lijuan Mao; Meiling Huang; Yiqu Wu; Shulin Zhuang; Shixuan Cui (Science of The Total Environment, 2023)

Comprehensive transcriptome analysis unravels the crucial genes during adventitious root development induced by carbon monoxide in Cucumis sativus L. - Fahong Yun; Dengjing Huang; Meiling Zhang; Chunlei Wang; Yuzheng Deng; Rong Gao; Xuemei Hou; Zesheng Liu; Weibiao Liao (Molecular Biology Reports, 2022)

Construction of mannose-modified polyethyleneimine-block-polycaprolactone cationic polymer micelles and its application in acute lung injury - Meiling Su; Heping Hu; Xuan Zhao; Chengyuan Huang; Bowen Yang; Zongning Yin (Drug Delivery and Translational Research, 2022)

Does lower regional density result in less CO2 emission per capita? - Yumei Lin; Junpei Huang; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Correction to: Reactive Oxygen Species–Responsive Celastrol-Loaded Bilirubin Nanoparticles for the Treatment of Rheumatoid Arthritis - Xuan Zhao; Chengyuan Huang; Meiling Su; Yu Ran; Ying Wang; Zongning Yin (The AAPS Journal, 2022)

Reactive Oxygen Species–Responsive Celastrol-Loaded Bilirubin Nanoparticles for the Treatment of Rheumatoid Arthritis - Xuan Zhao; Chengyuan Huang; Meiling Su; Yu Ran; Ying Wang; Zongning Yin (The AAPS Journal, 2022)

Role of gibberellin and its three GID1 receptors in Jasminum sambac stem elongation and flowering - Hongliang Zhang; Wei Wang; Jinfeng Huang; Yuting Wang; Li Hu; Yuan Yuan; Meiling Lyu; Binghua Wu (Planta, 2022)

Genome-wide investigation of microsatellite polymorphism in coding region of the giant panda (Ailuropoda melanoleuca) genome: a resource for study of phenotype diversity and abnormal traits - Meiling Cheng; Jianying Ren; Fujun Shen; Yan Huang; Zhenxin Fan; Megan Price; Bisong Yue; Xiuyue Zhang (Mammal Research, 2019)

Genome-wide identification of the pectate lyase-like (PLL) gene family and functional analysis of two PLL genes in rice - Yinzhen Zheng; Junjie Yan; Shuzhen Wang; Meiling Xu; Keke Huang; Guanglong Chen; Yi Ding (Molecular Genetics and Genomics, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Long noncoding RNAs in the mTOR signaling network: biomarkers and therapeutic targets - Tinglei Huang; Meiling Wang; Bo Huang; Augustus Chang; Feng Liu; Yanjie Zhang; Bin Jiang (Apoptosis, 2018)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Estimation of residue depletion of cyadox and its marker residue in edible tissues of pigs using physiologically based pharmacokinetic modelling - Lingli Huang; Zhoumeng Lin; Xuan Zhou; Meiling Zhu; Ronette Gehring; Jim E. Riviere; Zonghui Yuan (Food Additives & Contaminants: Part A, 2015)

Is the Hypoglycemic Action of Vanadium Compounds Related to the Suppression of Feeding? - Meiling Huang; Yaling Wu; Na Wang; Ziwei Wang; Pan Zhao; Xiaoda Yang (Biological Trace Element Research, 2014)

Vanadyl acetylacetonate upregulates PPARγ and adiponectin expression in differentiated rat adipocytes - Yaling Wu; Meiling Huang; Pan Zhao; Xiaoda Yang (JBIC Journal of Biological Inorganic Chemistry, 2013)

Development of a real-time RT-PCR method for rapid detection of H9 avian influenza virus in the air - Jing Lv; Baozhi Wei; Tongjie Chai; Xianzhu Xia; Zengmin Miao; Meiling Yao; Yuwei Gao; Rong Huang; Huili Yang; Uwe Roesler (Archives of Virology, 2011)